Utility of thoracic ultrasonography in a rapid diagnosis of angiostrongylosis in young dogs presenting with respiratory distress. (May 2021) - Venco, L.; Colaneri, G.; Formaggini, L.; De Franco, M.; Rishniw, M.
Highlights: Angiostrongylosis can cause respiratory distress, especially in young dogs. Lesions are frequently distributed within pulmonary subpleural zones. In dogs <2 years of age, thoracic ultrasonography can increase clinical suspicion. Point-of-care ultrasound might expedite diagnosis of pulmonary angiostrongylosis. Abstract: The nematode, Angiostrongylus vasorum is a nematode that lives in the pulmonary arteries of canids and has an obligate gastropod intermediate host. It can cause various clinical signs. with the two most common clinical scenarios consisting of acute respiratory distress and haemorrhagic diathesis, either separately or together. Younger dogs (< 2 years) are overrepresented, and dogs often show pulmonary granulomata (radiographically and pathologically). Thoracic ultrasonography offers a safe, rapid, commonly available, non-invasive means of assessing the lungs. We prospectively examined the utility of thoracic ultrasonography in the diagnosis of angiostrongylosis in 26 client-owned dogs <2 years old, presenting with respiratory distress. We identified small hypoechoic subpleural nodules in 15/26 dogs; 14 of these were subsequently confirmed to have angiostrongylosis by faecal Baermann concentration test, A. vasorum antigen testing or both. The remaining 11 dogs without subpleural nodules had negative faecal analysis and A. vasorum antigen testing and diagnosed with other respiratory diseases. This resulted in a sensitivity of 100% and a specificity of 92% for the detection of angiostrongylosis by thoracic ultrasonography in young dogs presenting with respiratory distress. Our results suggest that thoracic ultrasonography might offer a safe, rapid, relatively accurate diagnostic test for diagnosis of angiostrongylosis in young adult dogs with respiratory distress living in endemic areas.